Priorities of a Regional University Educational Activities Modernization - T. A. Olkhovaya; S. V. Pankova (Высшее образование в России, 2018)
The article is focused on the problem of educational programs modernization on the basis of principles of project-oriented training and students’ involvement in solving scientific-research and industrial-technological tasks relevant for the region. Special attention is paid to the multilevel career guidance work at Oreburg State University (special projects such as pre-university education centre “Applicant”, University Computer School, University physics and maths school, “University Saturdays”). The task of creating a complex of educational and intellectual products that ensure high competitiveness of university graduates is considered. For this purpose, the University reali- zes two educational projects: “School of leadership” and “Going to study at OSU”. These projects implement project-oriented training, involve employers in educational process. As a result, students present their own business projects with financial support. Special course of technological entrepreneurship is aimed at development of business thinking, business planning, management skills, key competences to start a business or to conduct innovation projects at companies. Modernization of educational practices gives considerable topical relevance to the question of young teachers and researchers retention at the University, their integration in academic community.